Spatial Econometrics From Cross-Sectional Data to Spatial Panels - Elhorst, J. Paul.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book provides an overview of three generations of spatial econometric models: models based on cross-sectional data, static models based on spatial panels and dynamic spatial panel data models. The book not only presents different model specifications and their corresponding estimators, but also critically discusses the purposes for which these models can be used and how their results should be interpreted.
Contents -- 1 Introduction -- 2 Linear Spatial Dependence Models -- for Cross-Section Data -- 3 Spatial Panel Data Models -- 4 Dynamic Spatial Panels: Models, Methods and Inferences -- References.
Keywords: Economics; Economics -- Statistics; Econometrics; Regional economics; Economics/Management Science; Regional/Spatial Science; Econometrics; Statistics for Business/Economics/Mathematical Finance/Insurance.